المتطلبات التدريبية لمدرسي المرحلة الإعدادية المتعلقة بمحتوى كتب الرياضيات وآليات تنفيذه وفقاً للمعايير العالمية - الزبيدي، أحمد محمد عبد; حسن، لينا فؤاد جواد الأمير (رابطة التربويين العرب, 2017)
يهدف البحث التعرف على المتطلبات التدريبية لمدرسي المرحلة الإعدادية المتعلقة بمحتوى كتب الرياضيات وآليات تنفيذه وفقاً للمعايير العالمية، تم الاستعانة بالمنهج الوصفي التحليلي لتحليل محتوى (NCTM) – المجلس القومي لمعلمي الرياضيات – لإعداد قائمة بمعايير الرياضيات المدرسية، كما استعان الباحثان بالمنهج الوصفي الدراسات المسحية لجمع المعلومات من مدرسي الرياضيات عينة البحث لتحديد المتطلبات التدريبية لديهم. تكونت عينة البحث من (30) مدرس ومدرسة من مدرسي مادة الرياضيات في المدارس الإعدادية والثانوية (ممن يدرسون المرحلة الإعدادية). قام الباحثان بإعداد أداة البحث المتمثلة باستبانة المتطلبات التدريبية تتكون من (34) فقرة تمثل كل منها مؤشرا لأحدى معايير الرياضيات المدرسية الخاص بمعايير المحتوى ومعايير العمليات كل فقرة يقابلها مقياس خماسي يتدرج من (5-1) درجة يحدد المتطلب التدريبي وهي (بدرجة كبيرة جداً، بدرجة كبيرة، بدرجة متوسطة، بدرجة قليلة، بدرجة قليلة جداً) تم تطبيقها على عينة البحث في الفصل الدراسي الثاني للعام (2015-2016م). استخدم الباحثان عدد من الوسائل الإحصائية المناسبة لإجراءات البحث وفي تحليل النتائج. أظهرت نتائج البحث عدم وجود حاجة تدريبية لمدرسي الرياضيات في مجال الإعداد والعمليات عليها وهو أحد مجالات محور معايير المحتوى، وأن هناك حاجة تدريبة ملحة لمدرسي الرياضيات في باقي مجالات محور معايير المحتوى والواردة بالترتيب التنازلي الآتي : (مجال الهندسة يليه مجال الجبروالدوال يليه مجال تحليل البيانات والاحتمال يليه مجال القياس)، وفيما يخص محور معايير العمليات فقد أظهرت النتائج أن هناك حاجة ملحة لجميع مجالات محور العمليات والواردة بالترتيب التنازلي الآتي : (مجال التعليل والبرهان يليه مجال حل المشكلات يليه مجال التمثيلات الرياضية والاحتمال يليه مجال التواصل الرياضي يليه مجال الترابط الرياضي). وفي ضوء النتائج توصل الباحثان إلى العديد من الاستنتاجات والتوصيات والمقترحات.
The research aims to identify the training requirements for teachers of preparatory phase on the content of math books and mechanisms The research aims to identify the training requirements for preparatory schools teachers that concerning on the content of math books and mechanisms of implement it, in accordance with international standards, the Descriptive analytical approach was used to analysis content of (NCTM) - National Council of Teachers of Mathematics to prepare a list of school math standards, the researcher hired also to the Descriptive approach of surveys to gather information from teachers of mathematics (research sample) to determine the training requirements they have got The research sample consisted of 30 teachers of math in preparatory and secondary schools (who is teaching in preparatory school) The researchers prepared the search tool of identifying training requirements which consist of (34) items, each of them represents an indicator of one's standards for school mathematics: content standards and processes standards each paragraph Offset by a five-scale of (5-1) score determines the requirement training, (a very large degree, highly, moderately, a low degree, very few degree) the tool was applied on the sample of research in the second semester of the academic year (2015 - 2016). The researchers used a number of appropriate statistical methods for research procedures and the analysis of its results results showed There was no need of training required for teachers of mathematics in the field of Numbers and their operations, one of the Centerpiece content standards, and showed there is An urgent need of training for Teachers of Mathematics in the rest of the Centerpiece content standards that contained countdown follows in order: (Geometry, followed Algebra and Functions field followed by data analysis and probability, followed by the field of measurement), and with Regarding to the Centerpiece of operations standards, the results showed that there is an urgent need for all the field of Centerpiece of operations contained countdown follows in order: (the field of reasoning and proof, followed by the field of problem solving, followed by The field of mathematical representations and probability, followed by the field of mathematical communication, followed by the field of mathematical interdependence In light of the findings the researchers reached several conclusions, recommendations and proposals.
Keywords: المرحلة الإعدادية -- معلم الرياضيات -- الكفايات التدريسية -- التدريب التربوي